2023
DOI: 10.1001/jamanetworkopen.2023.1993
|View full text |Cite
|
Sign up to set email alerts
|

Association of Posttraumatic Headache With Symptom Burden After Concussion in Children

Abstract: ImportanceHeadache is the most common symptom after pediatric concussion.ObjectivesTo examine whether posttraumatic headache phenotype is associated with symptom burden and quality of life 3 months after concussion.Design, Setting, and ParticipantsThis was a secondary analysis of the Advancing Concussion Assessment in Pediatrics (A-CAP) prospective cohort study, conducted September 2016 to July 2019 at 5 Pediatric Emergency Research Canada (PERC) network emergency departments. Children aged 8.0-16.99 years pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Similar findings were reported for children, the ratio of headache types was 1:3 (tension-type headaches:migraines) [ 38 ]. However, in other studies of both adults and children, the predominance of migraine-type headaches was reported [ 13 , 39 , 48 ]. Furthermore, it was shown that in mTBI patients experiencing PTH associated with blast trauma, most headaches were migraine-like types [ 51 ].…”
Section: Clinical Profiles Of Chronic Post-traumatic Headachementioning
confidence: 90%
See 3 more Smart Citations
“…Similar findings were reported for children, the ratio of headache types was 1:3 (tension-type headaches:migraines) [ 38 ]. However, in other studies of both adults and children, the predominance of migraine-type headaches was reported [ 13 , 39 , 48 ]. Furthermore, it was shown that in mTBI patients experiencing PTH associated with blast trauma, most headaches were migraine-like types [ 51 ].…”
Section: Clinical Profiles Of Chronic Post-traumatic Headachementioning
confidence: 90%
“…PTH most commonly resembles migraine-like and tension-type-like headaches [13,[19][20][21]39]; • Tension-type-like headaches are the most frequent in most PTH patients (75 to 77%) [40,41]; however, in others, migraine-type headaches predominate [13,19,22];…”
Section: Clinical Features Of Post-traumatic Headache (Pth)mentioning
confidence: 99%
See 2 more Smart Citations